Kinetics of calcium binding to dental biofilm bacteria. - Tarcísio Jorge Leitão (PLoS ONE, 2018)
Dental biofilm bacteria can bind calcium ions and release them during a pH drop, which could decrease the driving force for dental demineralization (i.e. hydroxyapatite dissolution) occurring at reduced pHs. However, the kinetics of this binding and release is not completely understood. Here we validated a method to evaluate the kinetics of calcium binding and release to/from Streptococcus mutans, and estimated the importance of this reservoir as a source of ions. The kinetics of calcium binding was assessed by measuring the amount of bound calcium in S. mutans Ingbrit 1600 pellets treated with PIPES buffer, pH 7.0, containing 1 or 10 mM Ca; for the release kinetics, bacterial pellets previously treated with 1 mM or 10 mM Ca were exposed to the calcium-free or 1 mM Ca PIPES buffer, pH 7.0, for up to 60 min. Binding and release curves were constructed and parameters of kinetics were calculated. Also, calcium release was assessed by exposing pellets previously treated with calcium to a pH 5.0 buffer for 10 min. Calcium binding to bacteria was concentration-dependent and rapid, with maximum binding reached at 5 min. On the other hand, calcium release was slower, and according to the calculations, would never be complete in the groups pretreated with 10 mM Ca. Decreasing pH from 7.0 to 5.0 caused a release of calcium able to increase the surrounding fluid calcium concentration in 2 mM. The results suggest that dental biofilm bacteria may act as a calcium reservoir, rapidly binding ions from surrounding fluids, releasing them slowly at neutral pH and promptly during a pH drop.